A puzzle for fools [large type] - Quentin, Patrick (Quentin, Patrick. Peter Duluth mystery., 2020)
"Broadway producer Peter Duluth sought solace in a bottle after his wife's death; now, two years later and desperate to dry out, he enters a sanitarium--but the institution doesn't quite offer the rest and relaxation he expected. Malevolent occurrences plague the hospital, and it soon becomes clear that a homicidal maniac is on the loose. With a hospital staff every bit as erratic as its idiosyncratic patients, it seems everyone is a suspect--even Peter's new romantic interest, Iris Pattison. Charged with solving the crimes by the baffled head of the ward, it's up to Peter to clear Iris's name before the killer strikes again."--Back cover.